1997
DOI: 10.1006/jcis.1997.4876
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Kinetics, Conformation, and Mobility of the Growth Hormone and Lysozyme on Solid Surfaces, Studied with TIRF

Abstract: Interactions of recombinant human growth hormone and lysozyme with solid surfaces are studied using total internal reflection fluorescence (TIRF) and monitoring the protein's intrinsic tryptophan fluorescence. The intensity, spectra, quenching, and polarization of the fluorescence emitted by the adsorbed proteins are monitored and related to adsorption kinetics, protein conformation, and fluorophore rotational mobility. To study the influence of electrostatic and hydrophobic interactions on the adsorption proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
122
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 27 publications
14
122
0
Order By: Relevance
“…In a previous publication 19 we reported that adsorption of hGH is dominated by hydrophobic interactions, as, for example, can be concluded when the hGH adsorption on the hydrophobic DDS is compared to that on hydrophilic silica. However, as shown in Figure 3a, both adsorption rates and amounts adsorbed are strongly reduced going from surfaces on which the alkyl chains are covalently attached (DDS and OTS) to surfaces on which the alkyl chains are physisorbed (ArAc and DPPC).…”
Section: Adsorption and Desorption Kineticsmentioning
confidence: 90%
See 2 more Smart Citations
“…In a previous publication 19 we reported that adsorption of hGH is dominated by hydrophobic interactions, as, for example, can be concluded when the hGH adsorption on the hydrophobic DDS is compared to that on hydrophilic silica. However, as shown in Figure 3a, both adsorption rates and amounts adsorbed are strongly reduced going from surfaces on which the alkyl chains are covalently attached (DDS and OTS) to surfaces on which the alkyl chains are physisorbed (ArAc and DPPC).…”
Section: Adsorption and Desorption Kineticsmentioning
confidence: 90%
“…19 All sorbent surfaces were prepared/cleaned within a few hours before use and mounted on top of a silicon rubber gasket which created a 0.5 mm space between the slide and an anodized aluminum support which could be filled with solutions. For slides covered with a surface layer of ArAc or DPPC head groups, this mounting was performed under water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a) is surprising in view of earlier studies 4,6,8,9,42,43 which reported that increasing ionic strength is causing a decrease in adsorption of lysozyme on silica surfaces. Tentatively, we attribute the observed insensitivity of the binding characteristics against salt to a compensation of two opposing effects: (a) increasing silanol dissociation due to the added salt; 45,46,49 (b) counter-ions of the salt competing with the protein for the charged surface sites.…”
Section: Protein Bindingmentioning
confidence: 94%
“…The experiments in the present study were carried out to investigate and compare the adsorption behaviour of these four proteins, under identical conditions, within the concentration ranges present in saliva (for lactoferrin and lactoperoxidase ≤10 g ml −1 [6,7], lysozyme ≤200 g ml −1 [6], and histatin 5 ≤45 g ml −1 [19]). Previously, studies have been performed on the adsorption of lactoferrin [20,21], lactoperoxidase [22] and lysozyme [20,[23][24][25][26][27], however these publications were carried out using different techniques to some extent, and additionally they were not performed using the same concentration ranges, buffer solutions (or, to some extent, substrates) as the present investigation. The adsorption behaviour of the four chosen proteins was investigated on two types of silica surfaces with different characters.…”
Section: Introductionmentioning
confidence: 99%